UV/VIS spectral properties of novel natural products from Turkish lichens - Yevgen Posokhov; Sule Erten; Ömer Koz; H. AnIl; Süheyla KIrmIzIgül; SIddIk Içli (International Journal of Photoenergy)
UV/VIS spectral characteristics of three new biologically active natural products, isolated from Turkish lichens, have been investigated in solvents of various polarity and proton donating ability. The effect of the solvent on spectral characteristics has been estimated. Quantum chemical calculations with the optimization of molecular geometry were done with the full-valent semiempirical methods AM1 and PM3 for conformational analysis and in order to discuss the charge distributions and dipole moments in the ground and in the excited states.